Optimum topology design of multi-material structures with non-spurious buckling constraints. (December 2017) - Doan, Quoc Hoan; Lee, Dongkyu
Highlights: Removal of spurious buckling modes is treated in optimal topology results. Modified versions of interpolation schemes remove the spurious buckling modes. Optimal multi-material steel composite topology design has buckling constraints. Numerical examples check the efficiency of the removal scheme in case multi-materials. MATLAB software easily solves a large number of computational routines problem. Abstract: This study contributes an investigation and a removal of spurious buckling modes which occur in optimal multi-material topology designs of steel composite using MATLAB computational software version 2017a. Using multiple steel materials within a structure provides many design possibilities to improve structural stability, especially, to prevent buckling phenomenon of the steel structure. Buckling effect and volume control are stated as constraints in the minimized compliance multi-material topology optimization problem. The multi-phase problem in this study is solved using an alternative active-phase algorithm with Jacobi version. The Method of Moving Asymptotes (MMA) is used to update the topology design variables which is relative element densities. The advantage of MATLAB software in solving a large number of routines problems which are eigenvalue and multi-material calculation routines and the MMA complex optimizer is shown through the numerical analysis in this study. Two material interpolation schemes controlling spurious buckling modes for the single material are modified for the present multi-material problem. The efficiency of each modified scheme for single and multiple steel materials are investigated and verified in numerical implementation.